PENGARUH LATIHAN SENAM AYO BERGERAK INDONESIA TERHADAP TINGKAT KEBUGARAN JASMANI SISWA PUTRA KELAS VIII SMP N 8 KOTA JAMBI - Deddy Rahmat Saputra (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2020)
Gymnastics is a sport that is carried out en masse, starting from the elementary, middle, upper, and public levels. In the past, gymnastics was very cultured, this is evidenced by the absence of differences in almost all circles of the gymnastics community both in groups and collectively, old, young, male, and female exercising together. This study aims to determine